2005
DOI: 10.1002/elps.200500096
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐locus variable number tandem repeats analysis for genetic fingerprinting of pathogenic bacteria

Abstract: DNA fingerprinting has attracted considerable interest as means for identifying, tracing and preventing the dissemination of infectious agents. Various methods have been developed for typing of pathogenic bacteria, which differ in discriminative power, reproducibility and ease of interpretation. During recent years a typing method, which uses the information provided by whole genome sequencing of bacterial species, has gained increased attention. Short sequence repeat (SSR) motifs are known to undergo frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
221
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(230 citation statements)
references
References 154 publications
0
221
0
9
Order By: Relevance
“…Three of the loci tested, STTR5, STTR6 and STTR10pl, displayed a high degree of polymorphism indicated by indices of 0.91, 0.92 and 0.84, respectively, which were comparable with published work (Lindstedt et al, 2004). One of the major drawbacks of this typing strategy is that the generation of variation in some MLVA loci is under selection pressure such that two identical clones may appear to differ if isolates have originated from different niches or from hosts with altered immune responses (Lindstedt, 2005). This may be manifested as too high a level of discrimination to correctly cluster isolates from a common source in an outbreak investigation.…”
Section: Q Wang and Othersmentioning
confidence: 92%
“…Three of the loci tested, STTR5, STTR6 and STTR10pl, displayed a high degree of polymorphism indicated by indices of 0.91, 0.92 and 0.84, respectively, which were comparable with published work (Lindstedt et al, 2004). One of the major drawbacks of this typing strategy is that the generation of variation in some MLVA loci is under selection pressure such that two identical clones may appear to differ if isolates have originated from different niches or from hosts with altered immune responses (Lindstedt, 2005). This may be manifested as too high a level of discrimination to correctly cluster isolates from a common source in an outbreak investigation.…”
Section: Q Wang and Othersmentioning
confidence: 92%
“…Considering that MLST is based on the variation in housekeeping genes that have a slow evolutionary clock and that the SIRU method looks into variable repeat regions that could evolve more rapidly by an introduction or deletion of a single repeat, clonal types might be affected by genomic rearrangements to different extents in the two methods. The SIRU loci in noncoding regions are less likely to be subject to natural selection that affects some VNTRs located on coding regions or promoters (43). Interestingly, among the seven SIRU loci, different evolutionary clocks could be observed, since SIRU01, SIRU07, SIRU13, SIRU15, and SIRU16 appeared to be generally monomorphic between strains from the same group and therefore more conserved during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Many bacterial genomes carry loci of repetitive DNA, which may contain variable repeated units among strains (43,60). Systems based on a multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) have been used extensively for typing of clinical isolates of several bacterial species and were shown to perform well compared to other genotyping methods (43,61).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of MLVA studies with other S. aureus typing methods have found that MLVA has advantages over pulsed-field gel electrophoresis (PFGE), spa typing and amplified fragment length polymorphism (AFLP) methods in reproducibility, discriminatory power and cost (Malachowa et al, 2005;Melles et al, 2009;Tenover et al, 2007;Vindel et al, 2009). MLVA is regarded as a well-recognized typing method (Lindstedt, 2005;van Belkum, 2007). MLVA provides genotypes expressed in strings of numbers corresponding to the number of repeats at each locus; therefore, this typing method produces results that are highly portable and easy to incorporate into an established database (Grissa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%